Analysis of Constructivism Philosophy in Academic Student Management at MAN Insan Cendekia Paser - Kirana, Ratih; Wardhana, Kautsar Eka (Poltanesa, 2023)
This study delves into the philosophical underpinnings of constructivism within the realm of student management. Constructivism, a pedagogical approach rooted in the belief that learners actively construct knowledge through their experiences, interactions, and reflections, has gained prominence in educational discourse. This research aims to critically examine how the principles of constructivism shape and influence the management of students in educational settings. The investigation employs a philosophical lens to scrutinize the core tenets of constructivism, exploring its implications for the design and implementation of effective student management strategies. By synthesizing educational philosophy and practical management methodologies, this study seeks to provide insights into how educators can leverage constructivist principles to enhance the overall learning experience for students. Through a comprehensive literature review and analysis, the research aims to contribute to the ongoing dialogue on the integration of philosophical perspectives into educational practices. By unraveling the connections between constructivism and student management, this study endeavors to inform educators, administrators, and policymakers about the potential benefits and challenges associated with adopting a constructivist approach in shaping the educational journey of students. The findings aim to guide educational stakeholders in fostering an environment that nurtures active learning, critical thinking, and meaningful engagement among students.